Unravelling the role of health-promoting and health-abusive lifestyle behaviours on health-related quality of life among the urban community-dwelling youths (19–25 years) in the Balasore district of Odisha, India - Akash Mallick; Abinash Sahoo (Discover Public Health)
Abstract Introduction Worldwide, the youth is becoming more vulnerable to compromised health and well-being, due to their growing engagement in several health-abusive lifestyle behaviours such as smoking, alcohol intake and problematic digital activity and limiting from essential health-promoting lifestyle behaviours such as healthy diet, physical activity and quality sleep. This study, hence, examines the trend and effects of such health-abusive and health-promoting behaviours on health-related quality of life of the youth. Methods The cross-sectional study used primary data from a sample of 124 urban community-dwelling youth (19–25 years) of Balasore district of Odisha during March–April, 2024. The study participants were selected through multi-stage sampling to obtain data on various health-promoting and health-abusive lifestyle behaviour patterns such as physical activity and sleep, health-abusive lifestyle behaviour patterns through self-administered structured questionnaire. Data analysis was performed with descriptive statistics and regression analysis. Results Among the study participants, majority reported problematic sleeping (60.5%), consumption of various fast-foods, in particular baked foods and desserts (82.3%) and snacks and savouries (75.8%). Prevalence of smoking was high (35.5%) while alcohol intake was low (8.1%). Around 59% were found as addicted to smartphone. Around 40 percent of the participants showed poor health-related quality of life, which was significantly associated with problematic sleeping, physical activity and smoking. Youth, who smoked [OR = 4405; 95% CI 1.662–11.670; p < 0.001] had significantly higher odds of showing poor health-related quality of life, while the youth not engaging in frequent sedentary physical activity [OR = 0.146; 95% CI 0.042–0.503; p < 0.005], and not reporting problematic sleeping [OR = 0.160; 95% CI 0.058–0.442; p < 0.001] showed lower odds. Conclusion Major highlights of the study were poor health-promoting lifestyle behaviours such as lack of physical activity and sleep disturbance among the youth, in addition to higher prevalence of health-abusive lifestyle behaviours such as fast-food consumption and smoking. This suggests on the prerequisite for effective intervention to strategically restrain the upsurge of health-abusive lifestyle behaviours among the youth.